Efficient high-resolution deletion discovery in Caenorhabditis elegans by array comparative genomic hybridization - Maydan, Jason S.; Flibotte, Stephane; Edgley, Mark L.; Lau, Joanne; Selzer, Rebecca R.; Richmond, Todd A.; Pofahl, Nathan J.; Thomas, James H.; Moerman, Donald G. (Genome Research, 2007)
We have developed array Comparative Genomic Hybridization for Caenorhabditis elegans as a means of screening for novel induced deletions in this organism. We designed three microarrays consisting of overlapping 50-mer probes to annotated exons and micro-RNAs, the first with probes to chromosomes X and II, the second with probes to chromosome II alone, and a third to the entire genome. These arrays were used to reliably detect both a large (50 kb) multigene deletion and a small (1 kb) single-gene deletion in homozygous and heterozygous samples. In one case, a deletion breakpoint was resolved to fewer than 50 bp. In an experiment designed to identify new mutations we used the X:II and II arrays to detect deletions associated with lethal mutants on chromosome II. One is an 8-kb deletion targeting the ast-1 gene on chromosome II and another is a 141-bp deletion in the gene C06A8.1. Others span large sections of the chromosome, up to >750 kb. As a further application of array Comparative Genomic Hybridization in C. elegans we used the whole-genome array to detect the extensive natural gene content variation (almost 2%) between the N2 Bristol strain and the strain CB4856, a strain isolated in Hawaii and JU258, a strain isolated in Madeira.
10.1101/gr.5690307